2013
DOI: 10.1097/wnr.0000000000000071
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide promotes neuronal differentiation of mouse embryonic stem cells in vitro

Abstract: Factors controlling proliferation and differentiation are crucial in advancement of neural cell-based experimental neurodegenerative therapies. In this regard, nicotinamide has been shown to determine the fate of neural cells, enhance neuralization, and influence DNA repair and apoptosis. This study investigated whether the biologically active vitamin B3 metabolite, nicotinamide, could direct the differentiation of mouse embryonic stem cells, cultured as monolayers, into neurons at either early or late stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Interestingly, it has recently been reported that BMP4 addition to optic cup differentiation cultures increases retinal genesis if added on day 6 [72], when further BMP inhibition would likely be detrimental [73]. In addition to utilizing the DID small molecule combination to promote differentiation to RGCs, we also observed that these molecules were additive with the previously identified FSK [16] and NIC [34][35][36]69] (DIDNF). Notably, together these molecules could induce RGC differentiation in the absence of Matrigel, an outcome that was not possible without them in adherent culture.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, it has recently been reported that BMP4 addition to optic cup differentiation cultures increases retinal genesis if added on day 6 [72], when further BMP inhibition would likely be detrimental [73]. In addition to utilizing the DID small molecule combination to promote differentiation to RGCs, we also observed that these molecules were additive with the previously identified FSK [16] and NIC [34][35][36]69] (DIDNF). Notably, together these molecules could induce RGC differentiation in the absence of Matrigel, an outcome that was not possible without them in adherent culture.…”
Section: Discussionmentioning
confidence: 53%
“…This novel study reports that nicotinamide is sufficient to induce accelerated neural specification from mESCs which further progressed to form GABAergic neuronal populations with enhanced efficiency and maturity. Results obtained in this study show fundamental effects of nicotinamide during the initial phases of ESC development, rather than at later stages of neuronal differentiation [ 26 ]. Within 2 days of culture, nicotinamide had dramatically reduced the number of Oct4-expressing pluripotent colonies and increased GFP fluorescence, thereby suggesting that nicotinamide accelerated the conversion of mESCs to a neuroectoderm fate.…”
Section: Discussionmentioning
confidence: 99%
“…Within 2 days of culture, nicotinamide had dramatically reduced the number of Oct4-expressing pluripotent colonies and increased GFP fluorescence, thereby suggesting that nicotinamide accelerated the conversion of mESCs to a neuroectoderm fate. Previous findings reported by Griffin et al demonstrated that treatment of mESC (46C Sox1 GFP reporter cell line) monolayer cultures with nicotinamide at the early onset of development decreased the total number of cells in cultures, resulting in a greater ratio of neurons to non-neuronal cells [ 26 ]. Specifically, by day 14 in this study, nicotinamide treatment (from day 0–7) reduced the populations of undifferentiated cells and Sox1GFP+ progenitors, in addition to reducing Oct4 and GFP expression in the cultures concomitant with enhanced expression of βIII-tubulin, indicative of accelerated neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, it markedly increases DNA synthesis and cell proliferation. Nicotinamide promotes neural differentiation of mouse embryonic stem cells, increasing the percentage of βIII‐tubulin‐positive neurons in culture (Griffin et al, ). The addition of nicotinamide to the culture medium promotes the growth of ultimobranchial C cells from chick embryos for at least 60 days and causes profound morphological changes, resulting in the formation of networks of dense neuronal fibers (Miura and Kameda, ).…”
Section: Primary Culture Of the Ultimobranchial Gland Of Chicksmentioning
confidence: 99%